An explorative study on document type assignment of review articles in Web of Science, Scopus and journals’ websites - Zhu Manman; Lu Xinyue; Chen Fuyou; Yang Liying; Shen Zhesi (Journal of Data and Information Science, 2024)
Accurately assigning the document type of review articles in citation index databases like Web of Science(WoS) and Scopus is important. This study aims to investigate the document type assignation of review articles in Web of Science, Scopus and Publisher’s websites on a large scale.